Narrative with enlightening tendencies in contemporary Islamic reform discourse: Origin, development and relapse - Hbaieb, Souhail (Münster journal for Islamic and philosophical studies, 2022)
This paper aims to clarify how a part of Muslim reformers’s discourse‭ ‬in the Arab world‭, ‬between the end of the nineteenth century and the first half of the twentieth century‭, ‬contained‭ ‬a new grand narrative through which some reformers‭, ‬led by Muhammad Abdo‭, ‬tried to establish an Islamic identity Influenced by‭ ‬the European Enlightenment as it was known in the seventeenth and eighteenth centuries‭. ‬This narrative arose in specific historical conditions marked by the infiltration of secular discourse into contemporary Arab thought‭. ‬However‭, ‬the changes in the Arab‭ ‬context during the twentieth century did not allow this narrative to develop and be enshrined in Arab culture‭. ‬On the contrary‭, ‬there was a clear setback with the dominance of the narratives of political Islam›s discourse‭.‬